2021
DOI: 10.3389/fpsyg.2021.628787
|View full text |Cite
|
Sign up to set email alerts
|

Academic Stress and Emotional Well-Being in United States College Students Following Onset of the COVID-19 Pandemic

Abstract: COVID-19 has resulted in extraordinary disruptions to the higher education landscape. Here, we provide a brief report on 295 students’ academic perceptions and emotional well-being in late May 2020. Students reported the high levels of uncertainty regarding their academic futures as well as significant levels of stress and difficulty coping with COVID-19 disruptions. These outcomes were related to the higher levels of neuroticism and an external locus of control. Female students reported worse emotional well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(151 citation statements)
references
References 31 publications
10
129
0
12
Order By: Relevance
“…The study findings were consistent with previous research in China, the United States, France, Serbia, Saudia Arabia, Bangladesh, and India which revealed increasing anxiety depression, and stress rates amongst college students during the pandemic of COVID-19 (Ma et al, 2020;Clabaugh et al, 2021;Husky et al, 2020;Kostić et al, 2021;Khoshaim et al, 2020;Islam et al, 2020;Saravanan et al, 2021). This psychological problem had different pathological mechanisms.…”
Section: Resultssupporting
confidence: 91%
“…The study findings were consistent with previous research in China, the United States, France, Serbia, Saudia Arabia, Bangladesh, and India which revealed increasing anxiety depression, and stress rates amongst college students during the pandemic of COVID-19 (Ma et al, 2020;Clabaugh et al, 2021;Husky et al, 2020;Kostić et al, 2021;Khoshaim et al, 2020;Islam et al, 2020;Saravanan et al, 2021). This psychological problem had different pathological mechanisms.…”
Section: Resultssupporting
confidence: 91%
“…The impact of gender on anxiety (albeit with only a very small effect size) mirrors the findings by Alemany-Arrebola et al (2020) among college students, where women had higher scores in trait and state anxiety; the latter accentuated in cases where a relative had died -thus showing that the stressful situation of the pandemic and remote learning together with a critical event such as the illness and death of a relative or friend due to COVID-19 increases anxiety levels (and-in the case of the original studyinfluences the perception of academic self-efficacy). A similar conclusion was reported in Turkey by Aslan et al (2020), where female (as well as less physically active) students displayed higher levels of perceived stress and by Karaman et al (2021), in Switzerland by Amendola et al (2021), and in the US (Business Wire, 2021;Clabaugh et al, 2021), while among teachers a similar trend was observed in the Basque Country (Ozamiz-Etxebarria et al, 2021). In the general population, three studies carried out in Italy (Mazza et al, 2020;Moccia et al, 2020) and Iran (Moghanibashi-Mansourieh, 2020) showed women's mental health to be more impacted than men's; on the other hand, research in China (Cao et al, 2020;Chen et al, 2020;Huang and Zhao, 2021) and a meta-analysis by Cénat et al (2021a) of papers again mainly hailing from this country found no gender differences in females' and males' experience of pandemic-related stressors.…”
Section: Discussionsupporting
confidence: 71%
“…To cope with stress and anxiety, participants sought support from others and helped themselves by adopting either negative or positive coping mechanisms. Clabaugh et al (2021) found that levels of stress and difficulty with coping with pandemic disruptions were related to neuroticism, an external locus of control, gender, and ethnicity, while a study from Mexico (Gaeta et al, 2021) discovered a relationship between university students' self-regulated learning and emotions such as tranquillity, hope, gratitude, joy, loneliness, and disinterest, mediated by coping strategies. A study by Alemany-Arrebola et al (2020) showed that college students with a higher level of anxiety expressed more negative emotions and declared lower academic self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, there was a switch to emergency online learning and second, face-to-face contact was reduced. Emergency remote teaching posed stressful challenges for many students and instructors (Clabaugh et al, 2021).…”
Section: Discussionmentioning
confidence: 99%